Amoxicillin Inactivation by Thiol-Catalyzed Cyclization Reduces Protein Haptenation and Antibacterial Potency - Pajares, María A.; Zimmerman, Tahl; Sánchez-Gómez, Francisco J.; Ariza, Adriana; Torres, María J.; Blanca, Miguel; Cañada, F. Javier; Montañez, María I.; Pérez-Sala, Dolores (Frontiers in Pharmacology, 2020)
Serum and cellular proteins are targets for the formation of adducts with the β-lactam antibiotic amoxicillin. This process could be important for the development of adverse, and in particular, allergic reactions to this antibiotic. In studies exploring protein haptenation by amoxicillin, we observed that reducing agents influenced the extent of amoxicillin-protein adducts formation. Consequently, we show that several thiol-containing compounds, including dithiothreitol, N-acetyl-L-cysteine and glutathione, perform a nucleophilic attack on the amoxicillin molecule that is followed by an internal rearrangement leading to amoxicillin diketopiperazine, a known amoxicillin metabolite with residual activity. Increased diketopiperazine conversion is also observed with human serum albumin but not with L-cysteine, which mainly forms the amoxicilloyl amide. The effect of thiols is catalytic and can render complete amoxicillin conversion. Interestingly, this process is dependent on the presence of an amino group in the antibiotic lateral chain, as in amoxicillin and ampicillin. Furthermore, it does not occur for other β-lactam antibiotics, including cefaclor or benzylpenicillin. Biological consequences of thiol-mediated amoxicillin transformation are exemplified by a reduced bacteriostatic action and a lower capacity of thiol-treated amoxicillin to form protein adducts. Finally, modulation of the intracellular redox status through inhibition of glutathione synthesis influenced the extent of amoxicillin adduct formation with cellular proteins. These results open novel perspectives for the understanding of amoxicillin metabolism and actions, including the formation of adducts involved in allergic reactions.